Analytical documentation of the artificial insemination programme of BRAC - Barua, Proloy (BRAC, 2019)
This paper intends to have feedback of the stakeholders of BRAC artificial insemination (AI) programme that could be useful for the programme. The findings show that implementers have to compete with other service provides in discriminatory manner. Unfair price war, violation of bilateral deal and of existing breeding policy by the government have been identified as the major challenges of BRAC for transferring the AI technology to the beneficiaries. Organizational and academic recognition are the main drivers of the AI volunteers to work for BRAC as social entrepreneur to enhance their social and economic status. Despite having challenges, BRAC has been performing well compared to government and other service providers in the AI market due to high conception rate, skill AI workers, doorstep service, close monitoring, .and strict management. However the extent of challenges of BRAC may be explored further all over the operating areas to take necessary measures by the programme for sustainability.